Peningkatan Kesehatan Masyarakat Melalui Pengolahan Sayuran Bervitamin Tinggi Di Desa Jampue Kecamatan Lanrisang Kabupaten Pinrang - Zamzam, Syamsiar; Yamin, Mayasari; Mutmainnah, Nurul; SC, Ummu Kaltsum (Hippocampus: Jurnal Pengabdian Kepada Masyarakat, 2022)
Lack of public attention about the impotance of nutritious food for health. Most people in the village have switched to fast food such as instant noodles and canned fish, so they forget that vegetables are rich in nutrients. Thus resulting in malnutrition such as Kwashiorkor, marasmus, anemia, goiter, hyponatremia, hypokalemia, and vitamin deficiency. This community service activity is based on empowering village communities through vegetable processing training. This activity aims to convey to the public about the importance of maintaining health by consuming vegetables that are high in vitamins. The result of the activities achieved are very high public interest, the the community knows the nutritional content of vegetables and the community knows how to process various tiger vegetables which are high in vitamins to prevent malnutrition from an early age.